VALUE ORIENTATIONS OF PEOPLE LEANING TOWARD DIFFERENT TYPES OF CULTURE - Rybak, Oksana (PSYCHOLOGICAL JOURNAL, 2018)
The article summarizes the most up-to-date scientific approaches to value orientations, reveals the importance of value orientations in the development of personality, highlights the influence of culture on the formation of value orientations. Two clusters of the studied subjects susceptible to different types of culture are empirically isolated. Their value orientations and the dependence of the formed values ​​on the type of culture to which they tend to be studied are investigated. The paper highlights both the scientific and applied value of research on cultural and value orientations in such broad areas as consumer research, international business, cross-cultural psychology, child development, international relations, anthropology and sociology. Further prospects of research of this problem are indicated. After analyzing different approaches to the typology of culture, we can see that culture consists of many subsystems and components of these subsystems that interact closely with each other. Each component is the necessary condition for the functioning of culture. Applying methods that do not violate the underlying relationships and allow us to distinguish simple blocks and describe important features inside these blocks. Thus, the selection of types of culture is a methodological method of its analysis and study. The isolation of such types of culture as traditional, modern and dynamically developing cultures makes it possible to elucidate the particularities of culture in general. The division of the culture as a system into simpler subsystems, which are characterized by certain features, allows us to analyze in detail the phenomenon of culture itself. In addition, this study emphasizes the importance of values ​​and value orientations as an inseparable characteristic of culture.